2002
DOI: 10.1006/jare.2002.0971
|View full text |Cite
|
Sign up to set email alerts
|

Nectar oasis produced by Agave marmorata Roezl. (Agavaceae) lead to spatial and temporal segregation among nectarivores in the Tehuacán Valley, México

Abstract: We investigated temporal and spatial segregation of nectarivores at Agave marmorata inflorescences in Tehuacán, México. Using survival analysis, a technique in which data are treated as censored, we found temporal segregation among insects, hummingbirds, and perching birds during the most nectar-limited time. Survivorship curves of hummingbirds and orioles were not significantly different from each other, however, temporal segregation was observed within hummingbirds according to body size and territorial beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…For example, Agave striata Zucc. (Rocha et al 2005) and Agave marmorata Roezl (Flores-Torres 2005, Ornelas et al 2002 are species from central Mexico that have been reported to produce nectar during the day to attract visiting hummingbirds.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Agave striata Zucc. (Rocha et al 2005) and Agave marmorata Roezl (Flores-Torres 2005, Ornelas et al 2002 are species from central Mexico that have been reported to produce nectar during the day to attract visiting hummingbirds.…”
Section: Discussionmentioning
confidence: 99%